Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Perilaku Konsumtif Masyarakat di Desa Masalle Kecamatan Masalle Kabupaten Enrekang - azis, nurazmiza; Idris Parakkasi; A. Syatir Sofyan (Universitas Islam Negeri Alauddin Makassar, 2024)
The purpose of this study is to explain the effect of financial literacy on the consumptive behavior of the people in Masalle Village, to explain the effect of lifestyle on the consumptive behavior of the people in Masalle Village, and to explain the effect of financial literacy and lifestyle on the consumptive behavior of the people in Masalle Village, Masalle District, Regency Enrekang. This research uses quantitative research methods. In taking the sample using the formula from Krejcie and Morgan with an error level of 5% so that 340 samples were obtained. Consumptive Behavior (Y) 7.153 > 1.652, Financial Literacy (X1) and Lifestyle (X2) have a significant (simultaneous) effect on Consumptive Behavior (Y) 74.036 > 3.042 people in Masalle Village, Masalle Sub-District, Enrekang District.